1979
DOI: 10.1159/000250781
|View full text |Cite
|
Sign up to set email alerts
|

Palmar- und Digitalvarikose mit rezidivierenden Thrombophlebitiden

Abstract: Venectasias of palms and fingers, more or less developed, occur relatively frequently in elderly people. Other terms are palmar and digital varicosis. This abnormality is rarely observed, but it is clinically important in the case of thrombophlebitis, appearing as small, painful, palpable nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Thrombosis usually manifests as solitary or multiple papules or nodules [1] . Our review found the fourth digit was affected 17 times and In addition to our case, the palm was the site of a thrombosed varix only twice; one case was secondary to an underlying hypercoagulable state [2] and the other to mechanical trauma [3] . The lesions are commonly bluish but may also be erythematous [4] or skin-coloured [5] , especially if the lesion is deep enough and the overlying skin is thicker or hyperkeratinised.…”
Section: Discussionsupporting
confidence: 49%
“…Thrombosis usually manifests as solitary or multiple papules or nodules [1] . Our review found the fourth digit was affected 17 times and In addition to our case, the palm was the site of a thrombosed varix only twice; one case was secondary to an underlying hypercoagulable state [2] and the other to mechanical trauma [3] . The lesions are commonly bluish but may also be erythematous [4] or skin-coloured [5] , especially if the lesion is deep enough and the overlying skin is thicker or hyperkeratinised.…”
Section: Discussionsupporting
confidence: 49%
“…During movement, such as gripping, flexing and leaning on the limb, the venous pressure is intermittently increased leading to hypertrophy of the smooth muscle layer of the venous wall. Moreover, in elderly people, the elasticity of the connective tissue wall is reduced thus weakening the veins [5].…”
Section: Discussionmentioning
confidence: 99%
“…We were able to trace 20 cases in total, most of which (15) were described in the English literature, in which 1 or more palmar digital nodules were caused by partial or complete thrombosis of digital veins (Table 1). [1][2][3][4][5][6][7] The patients were usually female, from a wide age spectrum, but most often between 35 and 65 years old. Apart from our second case, the nodules were always located on the palmar side of the digit.…”
Section: Discussionmentioning
confidence: 99%
“…12 Various authors suggest that digital venous thrombosis develops in a varix, causing obliteration of blood flow. 4,5 Other contributing factors, apart from changes in the vessel wall leading to venous thrombosis, are changes in the blood flow and hypercoagulability of the blood. It has been suggested that intraluminal stasis of blood flow can be caused by flexion of the fingers and possibly by wearing rings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation